2005
DOI: 10.1002/pds.1163
|View full text |Cite
|
Sign up to set email alerts
|

Cancer incidence in a general population of asthma patients

Abstract: Asthma was not associated with an increased risk of cancer. In fact, the risk of non-smoking related cancer was slightly reduced. However, we observed a small-elevated risk of lung cancer among asthmatic patients. Whether this result is a due to residual confounding and/or protopathic bias remains unclear. Further investigation is warranted to confirm or discard these associations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 41 publications
0
42
0
2
Order By: Relevance
“…Vesterinen et al [17] evaluated the correlation between a history of asthma and cancer by linking two Finnish registers. They found a slightly increased risk of cancer for asthmatic men (SIR = 1.12), whereas González-Pérez et al [18] reported no association. A positive association between atopic dermatitis and cancer risk was observed in a prospective study in Denmark (SMR = 1.5) as well as in a retrospective cohort study in Sweden observing 15,666 patients hospitalized for atopic dermatitis (SIR = 1.13), and a study in the UK (IRR = 1.49) [19,20,21].…”
Section: Resultsmentioning
confidence: 91%
“…Vesterinen et al [17] evaluated the correlation between a history of asthma and cancer by linking two Finnish registers. They found a slightly increased risk of cancer for asthmatic men (SIR = 1.12), whereas González-Pérez et al [18] reported no association. A positive association between atopic dermatitis and cancer risk was observed in a prospective study in Denmark (SMR = 1.5) as well as in a retrospective cohort study in Sweden observing 15,666 patients hospitalized for atopic dermatitis (SIR = 1.13), and a study in the UK (IRR = 1.49) [19,20,21].…”
Section: Resultsmentioning
confidence: 91%
“…Future analyses of markers of atopy should carefully examine associations by colorectal subsite. Large European record linkage studies comparing colorectal cancer incidence in patients with asthma with that in the underlying general population reported lower risk (16), higher risk (19,20), and no association (21). Of 6 other studies (1 cohort and 5 case-control) that examined associations with allergic conditions and included at least 100 cases of incident colorectal cancer, 4 reported no association (22)(23)(24)(25), 1 reported significantly lower risk with a history of any allergic condition (defined as including asthma; ref.…”
Section: Discussionmentioning
confidence: 99%
“…In the IWHS (15), having 2 or more allergic conditions was associated with approximately 40% lower colorectal cancer incidence. Although some studies of individual allergic conditions found associations with modestly lower risk of colorectal cancer (15)(16)(17)(18), others did not (19)(20)(21)(22)(23)(24)(25), or found lower risk of rectal cancer, but not colon cancer (26).…”
Section: Introductionmentioning
confidence: 99%
“…Research relating asthma and cancer did not reveal a consistent pattern of association, while the relationship between smoking, airflow obstruction and lung cancer is well recognised [19][20][21][22][23][24]. Cigarette smoking is the leading cause of lung cancer and is also the main cause of lung function impairment.…”
Section: Discussionmentioning
confidence: 99%